Evaluation of exclusive internal endoscopic drainage for complex biloma with transluminal and transpapillary stenting - Sakamoto, Jun; Ogura, Takeshi; Ueno, Saori; Okuda, Atsushi; Nishioka, Nobu; Hakoda, Akitoshi; Uba, Yuki; Tomita, Mitsuki; Hattori, Nobuhiro; Nakamura, Junichi; Bessho, Kimi; Nishikawa, Hiroki (Endoscopy International Open, 2024)
Background and study aims Biloma is treated endoscopically with endoscopic retrograde cholangiography (ERCP) or endoscopi ultrasound-guided transluminal biloma drainage (EUS-TBD). However, almost all previous studies have used both internal and external drainage. External drainage has the disadvantages of poor cosmetic appearance and self-tube removal. The aim of the present study was to evaluate the internal endoscopic drainage for complex biloma after hepatobiliary surgery with an ERCP- or EUS-guided approach, without external drainage.Patients and methods This retrospective study included consecutive patients who had bilomas. A 7F plastic stent was deployed from the biloma to the duodenum in the ERCP group and the metal stent was deployed from the biloma to the stomach in the EUS-TBD group.Results Forty-seven patients were enrolled. The technical success rate was similar between the groups (ERCP 94% vs EUS-TBD 100%, P=0.371); however, mean procedure time was significantly shorter in the EUS-TBD group (16.9 minutes) than in the ERCP group (26.6 minutes) (P=0.009). The clinical success rate was 87% (25 of 32 patients) in the ERCP group and 84% (11 of 13 patients) in the EUS-TBD group (P=0.482). The duration of median hospital stay was significantly shorter in the EUS-TBD group (22 days) than in the ERCP group (46 days) (P=0.038). There was no significant difference in procedure-associated adverse events between the groups.Conclusions In conclusion, ERCP and EUS-TBD are complementary techniques, each with its own merits in specific clinical scenarios. If both techniques can be performed, EUS-TBD should be considered because of the short times for the procedure, hospital stay. and biloma resolution.
Keywords: Pancreatobiliary (ERCP/PTCD); Endoscopic ultrasonography; Intervention EUS